Deepwater carbonate ion concentrations in the western tropical Pacific since 250 ka: Evidence for oceanic carbon storage and global climate influence. (11th April 2017) - Qin, Bingbin; Li, Tiegang; Xiong, Zhifang; Algeo, Thomas J.; Chang, Fengming
Abstract: We present new "size‐normalized weight" (SNW)‐Δ[CO3 2− ] core‐top calibrations for three planktonic foraminiferal species and assess their reliability as a paleo‐alkalinity proxy. SNWs of Globigerina sacculifer and Neogloboquadrina dutertrei can be used to reconstruct past deep Pacific [CO3 2− ], whereas SNWs of Pulleniatina obliquiloculata are controlled by additional environmental factors. Based on this methodological advance, we reconstruct SNW‐based deepwater [CO3 2− ] for core WP7 from the western tropical Pacific since 250 ka. Secular variation in the SNW proxy documents little change in deep Pacific [CO3 2− ] between the Last Glacial Maximum and the Holocene. Further back in time, deepwater [CO3 2− ] shows long‐term increases from marine isotope stage (MIS) 5e to MIS 3 and from early MIS 7 to late MIS 6, consistent with the "coral reef hypothesis" that the deep Pacific Ocean carbonate system responded to declining shelf carbonate production during these two intervals. During deglaciations, we have evidence of [CO3 2− ] peaks coincident with Terminations 2 and 3, which suggests that a breakdown of oceanic vertical stratification drove a net transfer of CO2 from the ocean to the atmosphere, causing spikes in carbonate preservation (i.e., the "deglacial ventilation hypothesis"). During MIS 4, a transient decline in SNW‐based [CO3 2− ], along with other reported [CO3 2− ] and/or dissolution records, implies that increased deep‐ocean carbon storage resulted in a global carbonate dissolution event. These findings provide new insights into the role of the deep Pacific in the global carbon cycle during the late Quaternary. Key Points: We present modern SNW‐Δ[CO3 2− ] calibrations and assess their reliability as an alkalinity proxy Rising [CO3 2− ] from MIS 5e to 3 and from MIS 7 to 6 implies a shift in CaCO3 deposition from shelves to the deep ocean A decline in [CO3 2− ] during MIS 4 may record increased deep‐ocean carbon storage